1998
DOI: 10.1182/blood.v92.2.402
|View full text |Cite
|
Sign up to set email alerts
|

Blood Dendritic Cells From Myeloma Patients Are Not Infected With Kaposi's Sarcoma-Associated Herpesvirus (KSHV/HHV-8)

Abstract: In recent studies, the sequence of Kaposi's sarcoma-associated herpes virus (KSHV) or human herpes virus-8 (HHV-8) was detected in dendritic cells (DC) of patients with multiple myeloma (MM). A concern was raised whether there is an causal association between the viral infection and development of these tumors. In the present study, we have examined DC generated from blood adherent cells from 8 Swedish MM patients at different clinical stages and 2 patients with monoclonal gammopathy of undetermined significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
2
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 13 publications
0
3
2
1
Order By: Relevance
“…These results reaffirm that our findings are not due to contamination or due to artifacts. In contrast to our results and those of others, many investigators have failed to detect the KSHV DNA in BM biopsies or in BM dendritic cell cultures in MM patients 9–16. These contrasting results may be attributable to differences in PCR methodology and in the sensitivity of the techniques used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results reaffirm that our findings are not due to contamination or due to artifacts. In contrast to our results and those of others, many investigators have failed to detect the KSHV DNA in BM biopsies or in BM dendritic cell cultures in MM patients 9–16. These contrasting results may be attributable to differences in PCR methodology and in the sensitivity of the techniques used.…”
Section: Discussioncontrasting
confidence: 99%
“…Two additional independent laboratories confirmed the presence of KSHV DNA sequences in MM biopsies 7, 8. However, other groups have not been able to confirm this association either in bone marrow (BM) biopsies or in dendritic cell cultures from either the BM or peripheral blood 9–14. All of these conflicting results are based on findings in MM patients from western countries.…”
mentioning
confidence: 99%
“…Differences in the experimental strategy adopted cannot explain the discrepancy observed between the current investigation and the studies reporting a positive association between AIDS-PCNSL and HHV-8/KSHV (11,33). At present, the reasons for such discrepancy are unclear and may be of multiple nature, as recently exemplified by the discrepancies among studies on the relationship between HHV-8/KSHV and multiple myeloma (29,32,42,44,48,51). Hovewer, independ-ently of the precise reasons accounting for the observed discrepancies, it should be stressed that defining a positive association between a tumor and a virus based solely on the results of high sensitivity molecular assays, in the absence of serological evidence, may be misleading (36).…”
Section: Discussioncontrasting
confidence: 59%
“…HHV-8 infection was initially found in bone marrow DC of patients with multiple myeloma ( Rettig et al, 1997 ). However, evidence since has concluded that bone marrow-derived ( Mitterer et al, 1998 ), peripheral blood mononuclear cell (PBMC)-derived ( Cull et al, 1998 ; Yi et al, 1998 ), and CD34 positive cell-derived ( Mitterer et al, 1998 ) DC from myeloma patients do not contain HHV-8 sequences. In fact, the absence of HHV-8 in DC of these patients increases the feasibility of an autologous, DC-based immunomodulatory therapy for multiple myeloma.…”
Section: In Hhv-8-associated Diseasementioning
confidence: 99%